p-Cimeno reduz dor oncológica através da modulação da via de analgesia endógena e correntes de cálcio - Santos, Wagner Barbosa da Rocha (2018)
Cancer pain is one of the most prevalent and difficult to treat symptoms in cancer patients. Conventional pharmacological therapies cause several adverse reactions and, mostly, do not promote effective pain control. Natural products have several pharmacological properties, including analgesic. Among the natural products it is p-cymene (PC), a monoterpene found in more than 100 types of essential oils of different plant species, including those of the genus Protium. This compound has antinociceptive activity already described in models of acute pain. For this reason, the objective of this study was to evaluate the antinociceptive effect of PC on the cancer pain model induced by Sarcoma 180 (S180) in rodents. Male Swiss albino mice weighing between 28 and 32 grams (Protocol CEPA / UFS: 03/2014), and male Wistar rats (200 and 300g) were used (Protocol UFMG: 233/2013). All experimental protocols were approved by the UFS and UFMG Animal Research Ethics Committee (CEPA). The tumor was induced by the administration of 106 S180 cells in 25 μL in the right hind paw of the animals. In this model, the effect of PC against mechanical hyperalgesia, spontaneous nociception and nociception induced by non-noxious palpation were evaluated. Histological and neurochemical changes were evaluated by histological and immunofluorescence analysis, respectively. In addition, the effects of PC on tumor growth, muscle strength and the existence of bone degradation in the tumor region were verified. The action of PC on calcium channels was evaluated by electrophysiological studies and the binding energies between PC and the various subtypes of calcium channels were obtained through Molecular Docking. The data were evaluated through analysis of variance (ANOVA) followed by the Tukey’s post-test for parametric data, and for non-parametric data by Kruskal-Wallis followed by the Dunn’s post-test, being considered significant when p<0.05. PC decreased the mechanical hyperalgesia (p<0.05), spontaneous (p<0.001) and non-noxious palpation (p<0.001) nociceptions, with no changes on tumor development, neuromuscular function, bone degradation or histopathological aspects of the paw. PC decreased Fos expression in the spinal cord (p<0.001) and increased the number of Fos positive cells in PAG (p<0.05) and NRM (p<0.01). PC also reduced the density of calcium channel currents (p<0.05), and when complexed with CaV1, CaV2.1, CaV2.2 and CaV2.3 calcium channels, obtained the negative binding energy values of -60.118, -59.60, -49.55 and -59.95 kcal/mol, respectively. These results suggest that PC reduces oncologic pain through the activation of the endogenous analgesia pathway and by modulation of calcium channels. These data demonstrate that PC presents potential for the development of alternatives in the treatment of chronic pain conditions, such as cancer pain. However, further studies are needed to better elucidate the pharmacological effects and safety of this compound.